Bibliometric Analysis of Game Research Trends in Elementary Learning and Self-Regulated Learning Skill - Primaestri, Wening; Akhyar, Muhammad; Sutimin, Leo Agung (Jurnal Prima Edukasia, 2023)
Self-regulated learning is a skill that is important to be taught to students because this skill is useful in their learning environment management to achieve the best learning outcomes. Thus, teaching this ability as early as possible is better, such as in elementary school. One alternative way to introduce and teach this skill is through games. This study aims to capture the relevant previous research landscape regarding the use of games in elementary school learning and for self-regulated learning from 2020 to 2023 using bibliometric analysis with the help of the VOSviewer application. The Scopus database was used to search for data with the keywords "games", "self-regulated learning", "elementary education," and "primary education," which were then refined to become 196 journal article publications. From the results of this analysis, it was found that the trend of publications about the use of games in learning had appeared in 2020, but about self-regulated learning, game-based learning, and elementary/primary education had only appeared in 2021. The research focus can be divided into four major topics, namely: (1) the use of game and game-based learning in primary education, (2) child development, and (3) the use of technology used in primary school education. Surprisingly, there hasn't been research on self-regulated learning in elementary education. Thus, further research and development on the topic can be done.